2010
DOI: 10.1007/s11745-010-3437-9
|View full text |Cite
|
Sign up to set email alerts
|

Acyl‐CoA Binding Protein Gene Ablation Induces Pre‐implantation Embryonic Lethality in Mice

Abstract: Unique among the intracellular lipid binding proteins, acyl-CoA binding protein (ACBP) exclusively binds long-chain fatty acyl-CoAs (LCFA-CoAs). To test if ACBP is an essential protein in mammals, the ACBP gene was ablated by homologous recombination in mice. While ACBP heterozygotes appeared phenotypically normal, intercrossing of the heterozygotes did not produce any live homozygous deficient (null) ACBP (−/−) pups. Heterozygous and wild type embryos were detected at all post-implantation stages, but no homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 74 publications
1
23
2
1
Order By: Relevance
“…However, the precise role of this protein in mammalian physiology remains elusive. Knock-out of the Acbp gene in mice has recently been reported to be embryonically lethal (33). This contradicts our findings and the report by Lee et al (32), which show that mice depleted of ACBP are viable.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the precise role of this protein in mammalian physiology remains elusive. Knock-out of the Acbp gene in mice has recently been reported to be embryonically lethal (33). This contradicts our findings and the report by Lee et al (32), which show that mice depleted of ACBP are viable.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, lipid analyses showed that they have a decreased amount of TAG on the fur compared with control mice, whereas TAG levels in the skin and liver were similar. While this paper was in preparation, a new report was published showing that disruption of ACBP in mice causes preimplantation embryonic lethality (33). The molecular basis for these findings, which are at odds with results from our laboratory and those from the nm1054 mice, is not clear.…”
mentioning
confidence: 86%
“…We have shown that the mice suffer from a delayed adaptation of the liver to weaning due to a delayed induction of lipogenic pathways. In contrast to our data, Kier and colleagues reported that targeted disruption of ACBP leads to embryonic preimplantation lethality ( 25 ). The reason for this is unclear, but it may be caused by differences in targeting strategies.…”
Section: Immunostaining Of Paraffi N-embedded Tissuescontrasting
confidence: 99%
“…Interestingly, studies on mice ACBPs had revealed that depletion of either the 10-kDa ACBP or ACDB3 (consisting of an ACB domain and a phosphotyrosine-binding domain) resulted in embryonic lethality [151,152].…”
Section: Embryo Developmentmentioning
confidence: 99%